The full constitutionality of state codes of external control process: a critical view at the ratio legis of the Complementary Federal Law Project nº 79/2022 - Novelli, José Carlos (2024)
The establishment of procedural rules of external control via formal and specific law passed by Parliament has the potential to stabilize, over time, the relations between the Courts of Accounts and their jurisdictions, with respect of the principle of legal certainty. In this context, the Brazilian legal system emerges in 2022, in an unprecedented and innovative way, the Code of External Control Process of the State of Mato Grosso. The paper aims to defend the full state legislative competence to regulate the matter in the light of constitutional provisions and precedents of the Federal Supreme Court. The work gains relevance as the complementary federal bill 79/2022 advances in the Chamber of Deputies, which aims, among other measures, to provide for general rules related to the process of external control of all federative entities. In the development of the article, the deductive technique is adopted and research is carried out on specialized bibliographic material, norms and jurisprudence. From the research carried out, it was verified, at the same time, (i) the full competence of the state legislature to rule on its respective external control process and (ii) traces of unconstitutionality in the complementary federal bill 79/2022 or in any other federal diplomas through which the Union will legislate on the external control process at the state level.